Da libertinagem no Brasil colonial: a construção da imagem amoral das mulheres na literatura de viagem (1611-1808) - Mello Júnior, Fernando Marques de [UNESP] (2015)
Along with the landing of the fleet led by Pedro Álvares Cabral in the American Continent, many European efforts arose intending to devise and establish the outlines of what would Brazil and its inhabitants be. Inside this foreigner construction of Brazil certain common grounds can be identified without great difficulty. The present work concerns with mapping one of those topics: the debauchery of women in Colonial Brazil. During the sixteenth century, the country's native women - recurrent characters in travel literature - would already surprise Old World readers with their erotic profligacy. However, it is in the early seventeenth century that the lust before attributed to the natives starts to definitely characterize women from colonial Brazilian society. It is intended, in the following pages, to describe how such a libertine image of Portuguese American women was built by the Europeans. To this end, the present work will deal with travel literature written between 1611, when François Pyrard of Laval's credited travel reports are published - the first written work to mention the depracy of the Portuguese Colony's women - and 1808, the years King John VI's court arrives in Rio de Janeiro and imposes profound changes in colonial society behavior